Multifunctional AIE-active polymers containing TPA-TPE moiety for electrochromic, electrofluorochromic and photodetector. (July 2019) - Lu, Qingyi; Yang, Caiyu; Qiao, Xin; Zhang, Xu; Cai, Wanan; Chen, Ye; Wang, Yan; Zhang, Wei; Lin, Xiaoxue; Niu, Haijun; Wang, Wen
Abstract: Four novel multifunctional electrochromic materials (PTT, PDTT, PNT and PDNT) based on tetraphenylethylene (TPE) and triphenylamine (TPA) units by Stille coupling reaction were prepared. Electrochemical impedance spectroscopy (EIS) measurements found that four polymers had low resistance values which improved their electrochemical and electrochromic properties. In addition, the maximum coloration efficiency (CE; η) value is 126 cm 2 /C at 1246 nm of PDTT, bleaching and coloring response times are 2.6 s and 1.6 s, respectively. There is no significant change of performance after a 100 cycle scanning. In addition to their excellent electrochromic properties, they also exhibit a strong aggregation-induced emission (AIE) effect. Furthermore, the fluorescence color of PDNT changed from bright green to black when voltage was applied from 0.0 to 1.6 V. Four polymers responded rapidly to light and they maintained stability over a 1000 s cycle. Highlights: Novel multifunctional electrochromic materials have been synthesized and studied. Polymers exhibit a strong aggregation-induced emission (AIE) effect. Polymers exhibit excellent electrochromic and high electrofluorochromic properties.